Spatiotemporal Variation Characteristics and Driving Factors of Nitrogen Use Efficiency of Wheat–Rice Rotation Systems in the Taihu Lake Region - Lu, Xiaosong; Ma, Lixia; Yu, Dongsheng; Chen, Yang; Wang, Xin (Frontiers in Soil Science, 2021)
During the past three decades, a large amount of nitrogen (N) fertilizers has been applied in the rice and wheat rotation system in the Taihu Lake region of southern China to achieve high yield, resulting in low N use efficiency (NUE). China is implementing the national strategy “fertilizer reduction with efficiency increase” to solve the serious ecological problems caused by excessive fertilization. However, the effects of N fertilizer reduction on soil fertility and their integrated effect on NUE of rice–wheat rotation systems in the Taihu Lake region are not fully understood. In this study, test fields with different soil-fertility qualities were selected in typical rice–wheat areas in the Taihu Lake region to perform a 2-year rice–wheat N fertilizer effect test to obtain the comprehensive quantitative relationship among the integrated fertility index (IFI), nitrogen application level (NA), and NUE. Through the investigation and spatial analysis of NA and IFI in the study area in 2003 and 2017, the spatial and temporal variation characteristics of NA and IFI in the study area in the past 15-year period were obtained, and this information was spatially coupled with the comprehensive quantitative relationship model of NUE to reveal the variation characteristics and driving factors of NUE in the study area. The result shows that the wheat and rice NA in the study area in 2017 increased by 35.5 and 8.4%, respectively, compared with 2003. Due to excessive fertilization, the soil nitrogen, phosphorus, and potassium content of cultivated land in the study area in 2017 was greater than that in 2003, especially soil-available phosphorus and potassium contents, whereas soil organic matter (SOM) content was reduced. The cultivated land IFI of the study area as a whole increased by 7.2% in the 15-year period. The NUE of rice and wheat rotation increased by 5.8% in 2017 compared with that of 2003 due to the improvement in crop varieties and N fertilizer yield benefits. The increases of NA and IFI both have negative correlations with the NUE improvement, and the NA increase has a greater impact. In addition, the terrain, soil type, texture, and parent material also affect the soil nutrient-preserving capability and, thus, affect the spatial variation of IFI and NUE improvement. These factors have greater influence on NUE improvement of wheat than rice. This study provides a novel and effective method for analyzing the spatial-temporal variation characteristics of NUE in the rice–wheat system and is conducive to guide precise fertilization and N fertilizer reduction based on the spatial analysis of NA with IFI and NUE.